1995
DOI: 10.1007/bf02506921
|View full text |Cite
|
Sign up to set email alerts
|

Toward community: A third position

Abstract: This essay addresses the insufficiency of modern science as the solution to the problems of human life. It is a critique of community theory and a constructivist proposal for a synthesis of the individuality and collectivity solutions to the Paradox of the One and the Many—designated as the Third Position. The Third Position is necessary for the postmodern period for there is a need to incorporate the goal of Equality (or Justice) into a paradigm based on Liberty and Fraternity. The Third Position is also call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 80 publications
0
46
0
1
Order By: Relevance
“…Issues of power, responsibility, rights, justice, and compassion can then be addressed under a unifying central core-a "vision." It is suggested that this transformational dynamic (the third position of Newbrough, 1995) has the potential to address some of the unanswered questions about empowerment (Cowen, 1994, p. 168).…”
Section: O We Need Leaders?mentioning
confidence: 98%
See 1 more Smart Citation
“…Issues of power, responsibility, rights, justice, and compassion can then be addressed under a unifying central core-a "vision." It is suggested that this transformational dynamic (the third position of Newbrough, 1995) has the potential to address some of the unanswered questions about empowerment (Cowen, 1994, p. 168).…”
Section: O We Need Leaders?mentioning
confidence: 98%
“…The models were developed as part of current, school-based, case-study material that focuses on preventing alienation for 10-to 14-year-old students. The first model furthers the theories of community as caring persons (Dokecki, 1992) in its third position (Newbrough, 1995) (Williams, 1992). This framework is then used to present a community-development application of the components of transformational community, extending the community concepts of McMillan and Chavis (1986) toward those similar to the empowerment-organizing features posited by Maton and Salem (1995), and the theoretical revisions of McMillan (1996).…”
mentioning
confidence: 97%
“…Underlying these principles is the notion that investigators outside the community must establish a collaborative partnership with the Mohawk community in the process of conducting research studies. Newbrough's (1989Newbrough's ( , 1992aNewbrough's ( , 1992bNewbrough's ( , 1995 perspective on a paradigm shift which redefines the notion of "community" is relevant here. He noted that the postmodern view of community centers on justice and fairness in which the emphasis is on "equality," "fraternity," and "liberty."…”
Section: Community-based Research Partnership: Guiding Principlesmentioning
confidence: 98%
“…Constructivism puts primary emphasis on the independence of the interpretation of each of their own experience and ways to build their lives and ideas (Newbrough, 1995;Roth, 1994;Gil-Perez et al, 2002;Mansour, 2009). However, before expecting lecturers to change their beliefs, they need to first be aware of them and then beliefs may be remained unconsciously (Crandall, 2000).…”
Section: Beliefs and Teaching Functionsmentioning
confidence: 99%